Modulating Effect of Paeonol on Piglets With Ulcerative Colitis - Wang, Shanshan; Bai, Miaomiao; Shu, Qingyan; Liu, Zhengan; Shao, Yirui; Xu, Kang; Xiong, Xia; Liu, Hongnan; Li, Yao (Frontiers in Nutrition, 2022)
Piglet enteritis is a major problem that needs to be solved urgently in modern pig production. Paeonol (Pae) has been used as a novel treatment option due to its good medicinal value. This study purported to elucidate the regulatory mechanism of Pae on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) in weaned piglets. A total of 36 crossbred (Duroc × Landrace × Yorkshire) weaned piglets were stochastically split into six groups: the control group, DSS group, 0.2% Pae group, 0.4% Pae group, 0.8% Pae group, and mesalazine group. The control and DSS groups were fed with a basic diet, the three Pae and mesalazine groups were fed with 0.2, 0.4, 0.8%, and 2 g mesalazine per kilogram of basic diet throughout the study. On the 15th day of the test period, the control group was gavaged with 10 ml of normal saline, while the remaining five groups were gavaged with 10 ml 5% DSS solution for 13 days. The study lasted for 27 days. The results showed that the 0.8% Pae group significantly increased the average daily feed intake (ADFI) and Occludin mRNA expression in the colon of piglets (P < 0.05). The 0.2% Pae group markedly increased the average daily gain (ADG) and zonula occludens-1 (ZO-1) mRNA expression (P < 0.05). In the 0.2% and 0.4% Pae groups, the feed-to-gain ratio (F/G) was significantly reduced and the mRNA expression levels of Caspase-8, respectively, markedly enhanced the mRNA expression levels of transforming growth factor-β (TGF-β) and interleukins-4 (IL-4) (P < 0.05). In the 0.8% Pae group, the relative abundance of Campilobacterota was significantly reduced (P < 0.05). In the 0.4% Pae group, the relative abundance of Firmicutes was notably increased (P < 0.05). In the 0.2 and 0.8% Pae groups, the relative abundance of Prevotella was markedly increased (P < 0.05). In the 0.2% Pae group, the contents of propionic acid, butyric acid, and valerate acid were markedly higher (P < 0.05). Thus, it is speculated that Pae may regulate the balance of anti-inflammatory/pro-inflammatory factors, improve intestinal tight junction expression, reduce apoptosis, and improve intestinal microflora structure and growth performance of piglets, thereby restoring intestinal barrier function and alleviating DSS-induced UC in piglets.